Utilization of renewable energy sources in desalination of geothermal water for agriculture - Tomaszewska, Barbara; Akkurt, Gulden Gokcen; Kaczmarczyk, Michał; Bujakowski, Wiesław; Keles, Nazli; Jarma, Yakubu A.; Baba, Alper; Bryjak, Marek; Kabay, Nalan (Desalination, 2021)
The agricultural sector, which is highly dependent on water, is urged to build on improved water management practices and explore available options to match supply and demand because of the water scarcity risks and a sustainable and productive agri-food chain. Geothermal water is an energy source used to generate electricity and/or heat. After harnessing its energy, the remaining water can be used as a water source for irrigation following treatment because of its high ionic content. Geothermal fields are mostly located in rural areas where agricultural activities exist. This would be a good match to decrease the transportation cost of irrigation water. The energy demand of the desalination process for agriculture is higher, requiring additional post-treatment processes. Fossil fuels to fulfill the energy requirements are becoming expensive, and greenhouse gas emissions are harmful to the environment. Thus, efforts should be directed towards integrating renewable energy resources into desalination process. This work focuses on presenting a comprehensive review of geothermal water desalination which is powered by renewable energy and provides specific cases from Turkey and Poland. Furthermore, possible new generation renewable energy systems in desalination are introduced, considering their potential application in the desalination of geothermal water for agricultural irrigation. •RE use in desalination of geothermal water for irrigation is reviewed.•A novel approach that integrates RESs into agri-food chain is presented.•Specific cases of geothermal water desalination from Turkey and Poland are given.•Possible new generation RESs in desalination by capacitive deionization are explored.•Advantages/disadvantages of RE use in geothermal water desalination are discussed.